The Effect of the 2014 Federal Housing Administration Loan Limit Reductions on Homeownership Decisions. Issue 2 (4th March 2019) - MacDonald, Daniel
ABSTRACT: Using data from the American Community Survey, this article assesses the effects of the 2014 Federal Housing Administration (FHA) loan limit reductions on homeownership decisions. Employing a difference-in-differences identification strategy, we find little evidence that the loan limit reductions caused an overall decline in homeownership rates. However, we do find that overall homeownership rates (as well as African American homeownership rates more specifically) increased in low-price parts of metropolitan statistical areas that experienced a loan limit reduction relative to high-price areas, suggesting that the lack of an overall effect may be because of changing decisions on where to own a home, not whether to own a home. This thesis is further supported by evidence of an increase in commuting times for residents in areas that experienced a limit reduction. Our findings contribute to the debate over how individuals respond and adapt their homeownership decisions to policy changes and credit constraints.